Incretin mimetics: a novel therapeutic option for patients with type 2 diabetes – a review - Knop FK (Dove Medical Press, 2010)
Katrine B Hansen1, Tina Vilsbøll2, Filip K Knop21Department of Clinical Physiology, Glostrup Hospital, University of Copenhagen, Denmark; 2Diabetes Research Division, Department of Internal Medicine F, Gentofte Hospital, University of Copenhagen, DenmarkAbstract: Type 2 diabetes mellitus is a metabolic disease associated with low quality of life and early death. The goal in diabetes treatment is to prevent these outcomes by tight glycemic control and minimizing vascular risk factors. So far, even intensified combination regimen with the traditional antidiabetes agents have failed to obtain these goals. Incretin mimetics are a new class of antidiabetes drugs which involve modulation of the incretin system. They bind to and activate glucagon-like peptide-1 (GLP-1) receptors on pancreatic beta-cells following which insulin secretion and synthesis are initiated. Since the compounds have no insulinotropic activity at lower glucose concentrations the risk of hypoglycemia – a well-known shortcoming of existing antidiabetes treatments – is low. Additionally, incretin mimetics have been shown to be associated with beneficial effects on cardiovascular risk factors such as weight loss, decrease in blood pressure and changes in lipid profile. Current clinical data on the two available incretin mimetics, exenatide and liraglutide, are evaluated in this review, focusing on pharmacology, efficacy, safety and tolerability. The review is built on a systematic PubMed and Medline search for publications with the key words GLP-1 receptor agonist, exenatide, liraglutide and type 2 diabetes mellitus up to January 2009.Keywords: glucagon-like peptide-1 (GLP-1), exenatide, liraglutide, type 2 diabetes